A diverse assembly : the debate on a Scottish parliament - Paterson, Lindsay (Edinburgh University Press, 1998)
The 1997 Scottish Referendum confirmed the wish of the Scottish people for their first Parliament in almost 300 years. In this book Paterson draws together a collection of the key arguments for and against the reinstating of a Scottish Parliament.